Ordinance No. 4, §§ 3-5, Granite Falls Town Council (1904) (Granite Falls, Washington). - (:unkn) unknown (My University, 1904)
Any person who shall in the usual walks of life, within the limits of the town of Granite Falls, carry any deadly weapon concealed about his person shall be deemed guilty of misdemeanor and upon conviction thereof shall be fined in any sum not more than twenty nor less than two dollars and costs of prosecution which costs shall be a part of the fine.Any person except a peace officer in the discharge of his duties who shall draw, exhibit or attempt to use any deadly weapon within the corporate limits of the town of Granite Falls upon, to, or against another person shall upon conviction thereof, be fined in any sum not more than fifty nor less than ten dollars, and the costs of prosecution, which costs shall be a part of the fine, or imprisonment in jail not more than twenty five, nor less than five days or by both fine and imprisonment at the discretion of the Court. Any person, except a peace officer in the discharge of his duties, who shall within the corporate limits of the Town of Granite Falls fire or discharge any gun, pistol or any other fire-arms, or who shall fire or explode any firecrackers, bombs, torpedeos, or any other explosive without first obtaining permission from the town council shall be deemed guilty of a misdemeanor, and upon conviction thereof shall be fined in any sum not exceeding Twenty dollars and the costs of prosecution which costs shall be a part of the fine.
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE